Cognitive biases that can limit the success of ITS Academies - Benussi, Fulvio Oscar (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
ITS Academy: under this new name, Parliament approved the law establishing the Tertiary System of Higher Technological Education with the aim of completing the implementation of the dual system of tertiary education in our country, which is currently lagging behind other European countries. In this article we will indicate the new elements of novelty of the new pathway compared to the Istituti Tecnici Superiori (Higher Technical Institutes), and we will reason why, due to the cognitive bias prevalent among potential participants, we do not foresee a significant expansion of enrolments in the ITS Academy.